2012
DOI: 10.1002/anie.201203897
|View full text |Cite
|
Sign up to set email alerts
|

Sequential CH Arylation and Olefination: Total Synthesis of the Proposed Structure of Pipercyclobutanamide A

Abstract: Hip to be square A strategy for assembling tetrasubstituted cyclobutanes is reported in the context of a short, protecting-group-free synthesis of the proposed structure of pipercyclobutanamide A. The route features sequential C–H functionalizations on an unactivated cyclobutane wherein C–C bonds to aryl and styrenyl groups are made one-by-one in a stereocontrolled fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
82
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(84 citation statements)
references
References 39 publications
0
82
1
1
Order By: Relevance
“…[11] Recently, Baran has shown that racemic tri- and tetrasubstituted cyclobutanes can be prepared from disubstituted cyclobutanes through sequential arylation and vinylation reactions, [12] using directing groups and catalytic conditions originally developed by Daugulis [11b, 13] and also popularized by Chen. [14] Baran’s synthesis of piperarborenine B showcased sequential cyclobutane C(sp 3 )–H activation to construct the unsymmetrical truxillate core.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[11] Recently, Baran has shown that racemic tri- and tetrasubstituted cyclobutanes can be prepared from disubstituted cyclobutanes through sequential arylation and vinylation reactions, [12] using directing groups and catalytic conditions originally developed by Daugulis [11b, 13] and also popularized by Chen. [14] Baran’s synthesis of piperarborenine B showcased sequential cyclobutane C(sp 3 )–H activation to construct the unsymmetrical truxillate core.…”
mentioning
confidence: 99%
“…Initial attempts at C–H activation using known conditions [12a] (Ar-I, Pd(OAc) 2 , Ag 2 CO 3 , tert -BuOH, 75 °C) provided the arylated product in 45% yield and incomplete conversion of starting material. Gratifyingly, we discovered that the yield was significantly improved by running the reaction ‘on water.’ [26] Thus, the combination of 3,4,5-trimethoxyiodobenzene, Pd(OAc) 2 , PivOH, and K 2 CO 3 on water gave the desired cyclobutane 7 in 69% yield.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among those successful examples of methylene C(sp3)-H bond activation, the reported studies were mainly focused on C-H arylation [4] , acetoxylation [5] , alkynylation [6] , alkylation [7] , 30 amidation [8] and alkoxylation [9] . In constrast to C(sp3)-H bond arylation and alkylation, methylene C(sp3)-H alkenylation [10] [15] [16] received less attention. Besides its extensive utility [11] in organic synthesis, olefin functional group also serves as key scaffold found in many natural products [12] and theraputic 35 drugs [13] .…”
mentioning
confidence: 99%
“…1 A number of methods have been developed for cyclobutane synthesis, 2 including photochemical [2+2] cycloadditions, 1c,d,3,4 catalyzed [2+2] cycloadditions, 4,5 cyclobutanone syntheses via ketenes, 6 ring expansion of cyclopropylcarbinyl precursors, 7 and cyclobutanes CH activation. 8 Despite advances, there remains a need for new approaches to functionalized cyclobutanes.…”
mentioning
confidence: 99%